Determinants of Water Sales Income at The PDAM of Trenggalek Regency - Astini, Natasya Dyah Putri; Suman, Agus (Journal of Development Economic and Social Studies, 2025)
Water sales are the main source of revenue for PDAM Trenggalek Regency. Although sales revenue continues to increase, the range of water sales services to customers still has not reached an optimal level. The purpose of this study is to analyze the effect of the number of customers, water prices, and rainfall on water sales revenue at the Regional Water Supply Company (PDAM) of Trenggalek Regency. This study uses multiple linear regression analysis with secondary data for 2020-2024 sourced from PDAM Trenggalek Regency and the Central Statistics Agency (BPS). The results showed that partially the number of customers and the price of water have a positive and significant effect on water sales revenue, while rainfall has no significant effect on water sales revenue, and simultaneously, both the number of customers, the price of water, and rainfall together affect water sales revenue at PDAM Trenggalek Regency. PDAM Trenggalek Regency needs to focus on strategies to expand the number of customers and provide affordable water prices for the community. This research can be used as a reference material in making strategic decisions related to PDAM management and operational planning.